Making a Change from Below: A Comparative Study of Popular Movements for Reducing Waste and Promoting Cycling - Ličen, Daša; Podjed, Dan (Traditiones, 2020)
The authors look into two environmental movements that arose from grassroots initiatives. The first is Ecologists without Borders, the leading NGO promoting waste reduction in Slovenia. The second is Critical Mass, an international cyclists’ movement that seeks more public space for urban cyclists, which the authors studied in Belgrade and Budapest. Ethnographic analysis indicates that the two movements have had certain common experiences. The authors use these cases to investigate the social transition that such movements support and shed light on how they arise, function, and change over time.